The management of cultural institutions and their image on the basis of the institutions of wrocław municipality - Mroz-Gorgon, B. (Видавництво Львівської політехніки, 2013)
The essence of the problem in the present market environment is the adjustment of the cultural institution’s offer to modern culture audience – their requirements and tastes. In order to fulfil the difficult task of managing such institutions, the leaders need to constantly follow the missions of these institutions and – at the same time – manage them in a “marketoriented” way and consciously create their image. One of the responses to the present culture consumers’ trends in experiential marketing. Суть проблеми в реальних ринкових умовах полягає у коригуванні пропозиції культурних закладів відповідно до сучасної культурної аудиторії – їхніх вимог і смаків. Для того, щоб виконати важке завдання управління такими установами, лідери повинні постійно стежити за місіями цих установ і управляти ними «ринковим» методом, свідомо створюючи свій імідж. Одна з відповідей на тенденції нинішніх споживачів культури полягає в емпіричному маркетингу.
Управління закладами культури та їхнім іміджем на основі установ органів місцевого самоврядування Вроцлава
Keywords: management; image; promotion; cultural institutions; управління; імідж; просування; культурні інституції